Identity chains in newspaper cartoon narratives: an integrative model. Issue 1 (2nd January 2020) - Abdel-Raheem, Ahmed
Abstract: The literature on political cartoons and narrative has revolved around the question of how single-panel images can have narrative potential. This rests on the apparently erroneous assumption that most editorial cartoons, in contrast to comic strips or comic books, lack a continuing story arc that plays out over an n -issue series. Thus, drawing primarily on cognitive discourse analysis and social semiotic theories, this article focuses on the diachronic/temporal tracking of global texture and coherent narrativity in political cartoons. Specifically, it proposes that every cartoon panel is a portion of a narrative, and hence examines how narrative entities (including people, places, and things) are cohesively tied together as cartoon stories unfold. The integrative approach is illustrated on the basis of an analysis of 20 cartoons published in the Egyptian newspaper Al-Ahram .